ANALISIS INVESTASI PENGADAAN ALAT BERAT DI PT. KARBINDO ABESYAPRADHI DENGAN METODE NPV DAN IRR - Rizto Salia Zakri; Murad Murad; Sumarya Sumarya (Departemen Teknik Pertambangan FT UNP, 2014)
Abstract This research start from the condition in the field in PT. Karbindo Abesyapradhi, where the heavy equipment damage to often, it make production target never reach. To reach the target, is important to buy some new heavy equipment, but it can make some problem about the cost of investment. There are 3 option to buy some new heavy equipment, one of the option will be a best option and can make the company get profit. For this problem the writer make this research, to know the best alternative to the company.In this research the writer use quantitative research method and also use descriptive method. From this reseach we will know comparation from each option. Sample will represent all of heavy equipment of PT. Karbindo Abesyapradhi have.Based on this research, we know that buy a new heavy equipment cash is the best option for the company, where the company will get benefit from this option. This result become from trial with Net Present Value method, where the cash option get the higgest NPV value, while when we test with Internal Rate of Return after pass the incremental analitysis produce the result that the cash option be a best option and have the most benefit for the company and it can apply for all kind of heavy equipment in PT. Karbindo Abesyapradhi. Kata kunci : Investment, Heavy Equipment, NPV, IRR, Incremental Analysis